Toxicity and ovicidal activity of different entomopathogenic fungi, Hirsutella extracts on Tetranychus urticae (Acari: Tetranychidae) - Suradet Buttachon; War War May Zin (Persian Journal of Acarology)
Crude ethyl acetate extracts of six entomopathogenic fungi, Hirsutella species were screened against Tetranychus urticae Koch (Acari: Tetranychidae). In this study, all extracts presented potential to control eggs and adult female activities. Laboratory evaluation of the crude extracts of Hirsutella citriformis, H. guignardii, H. petchabunensis, H. satumaensis, H. saussurei and H. thompsonii showed slightly toxicity and median lethal concentration (LC50) values of 7,579.94, 8,910.38, 8,579.45, 5,055.96, 1,555.46 and 44,197.85 mg/L at 72 h after treatment against adult females of T. urticae, respectively. Related LC50 values that exhibited on eggs were 12,701.86, 30,922.72, 10,870.96, 12,635.56, 9,244.59 and 22,676.66 mg/L at 5 days after exposure. The most effective on T. urticae eggs and adult females is H. saussurei. Moreover, all extracts deceased the fecundity of T. urticae after being fed with mulberry leaf discs treated the crude extract of six species of Hirsutella under residual effect bioassay. The results suggest that the ethyl acetate extracts of Hirsutella citriformis, H. guignardii, H. petchabunensis, H. thompsonii, H. satumaensi and H. saussurei have the potential to be used for the control of T. urticae in the future.